Em busca do doce sabor - Soeiro, Teresa (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
This paper discusses the relevance of honey in the feeding habits and the implementation in Portugal, particularly in the northern area, of the apical science. This phenomenon will question, from the 19th century on, the traditional type of bee-keeping, using tubular cork bee-hives, by introducing the new international hives with movable frames. In Rio Mau (Penafiel) an industry of apical equipment was established from the early 20th century. This industry, set up under the influence of Manuel Tavares de Sousa, is still one of the major apical devices suppliers worldwide.